Well-controlled gestational diabetes mellitus without pharmacologic therapy decelerates weight gain in infancy - Li, Chao; Cai, Yixi; Li, Yinying; Peng, Bin; Liu, Yongfang; Wang, Zhenming; Yang, Ting; Hu, Yirong; Fu, Yajun; Shi, Tingmei; Peng, Hong; Zhang, Yue; et al. (Frontiers in Endocrinology, 2022)
Abstract Aim: There are no prospective longitudinal studies on the association between well-controlled gestational diabetes mellitus (GDM) without pharmacologic therapy and the physical growth of offspring in infancy. We aimed to identify the trajectories in physical growth (from 0–12 months of age) in the offspring of mothers with well-controlled GDM without pharmacologic therapy in a prospective cohort in developing countries. Methods: This study included 236 offspring of mothers with GDM and 369 offspring of mothers without GDM. Mothers with GDM were not on pharmacologic therapy. The length and weight of all infants were measured at 0, 1, 3, 6, and 12 months. Linear mixed-effect models and linear mixed-effect models were applied. Results：The fully adjusted model showed that the WAZ, LAZ, and BMIZ were similar at birth for the GDM and control groups and that increases in WAZ and BMIZ at 0–1, 0–6, and 0–12 months in the GDM group lagged behind those of the control group. Conclusions: Well-controlled GDM without pharmacologic therapy may normalize physical growth of offspring at birth and decelerate their weight gain in infancy. Whether glycemic control can mitigate the long-term effects of GDM on the growth trajectory in offspring remains unclear.